Computational investigation of binding mechanism of substituted pyrazinones targeting corticotropin releasing factor-1 receptor deliberated for anti-depressant drug design. Issue 12 (13th August 2019) - Shekhar, Mishra Shashank; Venkatachalam, T.; Sharma, Chandra Shekhar; Pratap Singh, Hemendra; Kalra, Sourav; Kumar, Neeraj
Abstract: In spite of various research investigations towards anti-depressant drug discovery program, no one drug has not yet launched last 20 years. Corticotropin-releasing factor-1 (CRF-1) is one of the most validated targets for the development of antagonists against depression, anxiety and post-traumatic stress disorders. Various research studies suggest that pyrazinone based CRF-1 receptor antagonists were found to be highly potent and efficacious. In this research investigation, we identified the pharmacophore and binding pattern through 2D and 3D-QSAR and molecular docking respectively. Molecular dynamics studies were also performed to explore the binding pattern recognition. We establish the relationship between activity and pharmacophoric features to design new potent compounds. The best 2D-QSAR model was generated through multiple linear regression method with r 2 value of 0.97 and q 2 value of 0.89. Also 3D-QSAR model was obtained through k-nearest neighbor molecular field analysis method with q 2 value of 0.52 and q 2 _se value of 0.36. Molecular docking and binding energy were also evaluated to define binding patterns and pharmacophoric groups, including (i) hydrogen bond with residue Asp284, Glu305 and (ii) π–π stacking with residue Trp9. Compound11i has the highest binding affinity compared to reference compounds, so this compound could be a potent drug for stress related disorders. Most of the compounds, including reference compounds were found within acceptable range of physicochemical parameters. These observations could be provided the leads for the design and optimization of novel CRF-1 receptor antagonists. Communicated by Ramaswamy H. Sarma GRAPHICAL ABSTRACT: ABBREVIATIONS: CRF corticotropin-releasing factor HPA hypothalamus-pituitary-adrenocortical axis kNN MFA k-nearest neighbor molecular field analysis MD molecular dynamics MLR multiple linear regression MM/GBSA molecular mechanics/generalized Born surface area OLS ordinary least squares regression OPLS optimized potential for liquid simulations POPC 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine QSAR quantitative structure-activity relationship RMSD root mean square deviation RMSF root mean square fluctuation SA simulated annealing XP extra precision